THE MODIFICATION OF ISLAMIC RELIGION LEARNING THROUGH SEKOLAH PENGGERAK CURRICULLUM - Nislawati, Ade; Sari, Dewi Purnama; Karolina, Asri; Siswanto, Siswanto (Nurul Jadid University, Paiton Probolinggo, East Java, 2022)
PAI Learning Modification is an effort made to create and display something new, unique, and interesting. This study aims to reveal in depth about the modification of PAI learning in the curriculum of the driving school. This study uses qualitative research using a case study approach. The informants of this research were the principal, curriculum representative, PAI Motivator Teacher, and students. This data collection technique uses the method of observation, interviews, and documentation. The validity of the data was tested by using source triangulation and technique triangulation. and data analysis techniques using the Miles and Huberman model, namely data reduction, data presentation, verification (drawing conclusions). The results obtained are first, the curriculum used previously was the 2013 curriculum based on the competencies formulated from the SKL. Second, PAI learning has not changed the same as the previous curriculum in PAI learning, which focuses on exploring the basic material of the curriculum, providing flexibility for educators, but with a higher understanding of the discussion of learning materials, including Akidah Akhlaq, Qur'an-Hadith, Fiqh and the history of Islamic culture (SKI). in the learning process supports the development of competence and character of students holistically, the teacher is a facilitator everything starts from the student self and is student-centered. Third, the modification of PAI learning in the curriculum of the driving school includes adjustment of learning achievement standards, the flow of learning objectives (ATP) has the same function as the syllabus, and the teaching module is the same as the lesson plan. fourth, the process of achieving learning objectives can be seen from the assessment or assessment, namely early diagnostic assessment of learning, formative assessment of ongoing learning and summative assessment, namely assessment at the end. The learning process between the previous curriculum and the driving school is very different in terms of the curriculum, the material is divided into phases, and in terms of assessment. Student learning activities are more active and independent